Aprendizagem baseada em problemas na religação de saberes no aprender a gerenciar em enfermagem - Campos, Leonara Raddai Gunther de (2013)
The object defined for this study is how the methodology of Problem Based Learning (PBL) allows the (re)connection of knowledge for nursing management, and promotes learner autonomy in the process of learning to learn. Our objectives were to understand how PBL enables (re)connection of knowledge for nursing management, and understand how PBL promotes the development of learner autonomy in the process of learning to learn, based on theoretical Liberating Pedagogy of Paulo Freire and Complex Thought in Edgar Morin. Our assumptions are that PBL contributes to significant learning of the student, providing opportunities for (re)connection of knowledge necessary to communicate, work in teams, to lead and resolve conflicts, and also favors the development of learner autonomy in making him able to construct their own learning. We conducted a qualitative study and the method used was Do It Yourself. The subjects were students and tutors involved in the discipline. Data collection techniques combined semi-structured interviews, participant observation, document analysis, log in portfolios by students, student evaluation forms, and audio recording of the tutorials. Data analysis followed interpretation strategies adopted by the authors, following the steps: 1) Initial readings; 2) Depth reading, 3) Construction of maps of meanings; 4) Reunion of the maps; 5) Development of empirical categories that were analyzed the light of the theoretical. We found that PBL provides continuous learning, developing student autonomy in the process of learning to learn. We emphasize the (re)connection of knowledge for nursing management, such as: leadership, communication, teamwork, planning, among others, mediated by small group work. The development of learner autonomy was also evident during the application of PBL, the student taking the lead role was a process that occurred gradually, leading him to experience changes related to knowledge forms of (re) construction of knowledge itself, promoted by the use of prior knowledge, the exercise of theorizing, the rewiring of knowledge in an interdisciplinary format, and the autonomy of the student in search of relevant knowledge. Challenges in the initiative to implement PBL in an adverse environment are numerous. It is a process that requires paradigmatic ruptures and openness to innovation, both by institution and by teachers and students. The PBL favors the opportunity to know what is known and thus lifelong learning, encourages student to develop the critical sense of reality, and its formation is not developed exclusively at academic level, but also at human and social ones.